THE ROLE OF THE MASS MEDIA IN THE FORMATION OF POLITICAL CONSCIOUSNESS OF THE YOUTH OF UZBEKISTAN - Ibodulla Kungirov (Journals Park Publishing, 2022)
This article examines the influence and role of the media on the development of the spiritual formation and political identity of young people, its importance in bringing up a harmoniously developed generation.
Keywords: mass media; social relations; political institutions